An experimental study on the incentives of the probabilistic serial mechanism - David Hugh-Jones; Morimitsu Kurino; Christoph Vanberg (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2013)
We report an experiment on the Probabilistic Serial (PS) mechanism for allocating indivisible goods. The PS mechanism, a recently discovered alternative to the widely used Random Serial Dictatorship mechanism, has attractive fairness and efficiency properties if people report their preferences truthfully. However, the mechanism is not strategy-proof, so participants may not truthfully report their preferences. We investigate misreporting in a set of simple applications of the PS mechanism. We confront subjects with situations in which theory suggests that there is an incentive or no incentive to misreport. We find little misreporting in situations where misreporting is a Nash equilibrium. However, we also find a significant degree of misreporting in situations where there is actually no benefit in doing so. These findings suggest that the PS mechanism may have problems in terms of truthful elicitation.
Keywords: C78; C91; C92; 330; probabilistic serial mechanism; incentives